FINANCING MECHANISMS OF INNOVATIVE PROJECTS THROUGH COMMERCIAL BANKS (Conferencea, 2023)
It is difficult to develop the socio-economic life of the country without small business entities and their innovative projects, the role of commercial banks in their financing is important. The reason is that commercial banks provide innovative project-producing and service-providing companies with credit funds, play a key role in the financing of innovative projects in our country, and thereby contribute to the general macroeconomic stability of the society.